Determination and Evaluation of Local Site Factors in Zeytinburnu, Istanbul, Turkey: A Scenario-Based Study - Sisman, Rafet (SPRINGER HEIDELBERG, 2022)
This study aims to present a reliability assessment of local site factors provided by the valid seismic code of Turkey (i.e., Building and Earthquake Code of Turkey-2019, BECT-2019). For this purpose, the Zeytinburnu district of Istanbul, which has been an active subject for microzonation projects, is investigated. The seismicity of the Zeytinburnu district and geotechnical properties of the soil sites are presented. The local site factors (i.e., F-S: the local site factor corresponding to 0.2-sec period and F-1: the local site factor corresponding to 1.0-sec period) are determined by using two different approaches. The local site factors are firstly determined with respect to the BECT-2019 and then by using site response analyses. Finally, the local site factors obtained by using the two approaches are compared. It can be noted that the F-1 values provided by the BECT-2019 are generally conservative, while the F-S values provided by the BECT-2019 are not.
Keywords: Local site factors; Earthquake design spectra; Site response analysis; The Zeytinburnu district; SEISMIC HAZARD; AMPLIFICATION; REGION; Science & Technology - Other Topics